Effect of Intention to Squat Explosively on Acute Countermovement Jump Performance. Issue 12 (5th December 2021) - O'Grady, Mathew W.; Young, Warren B.; Behm, David G.; Talpey, Scott W.
Abstract: O'Grady, MW, Young, WB, Behm, DG, and Talpey, SW. Effect of intention to squat explosively on acute countermovement jump performance. J Strength Cond Res 35(12): 3348–3354, 2021—The purpose of this study was to investigate the influence of squatting with the intention of moving the bar as fast as possible during the ascent phase on potentiating countermovement jump (CMJ) performance. Fourteen recreationally resistance-trained men (age = 22.1 ± 1.7 years, height = 179.9 ± 4.2 cm, body mass = 83.8 ± 6.6 kg) with a predicted 1 repetition maximum half-squat of 201.0 ± 27.8 kg participated in this study. Subjects performed 3 CMJs before and then 4 and 8 minutes after a squat conditioning activity (CA). Conditions were randomized. For 1 condition, the CA involved subjects performing 4 repetitions of the half-squat with a 5RM load in a controlled manner (CON) at a self-selected normal squatting tempo. In the other condition, subjects used the same number of repetitions and load; however, they were instructed to move the bar up as fast as possible during the concentric phase of the half-squat (VMAX). Half-squat peak force (N), peak power (W), peak velocity (m·s −1 ), and rate of force development (RFD) were measured for each CA using a force platform and linear position transducer. At 4 and 8 minutes post-CA, CMJ height, relative peak power, peak velocity, and peak force were also measured. Despite there being significant increases in the half-squat peak power, peak velocity and maximum RFD in the VMAX condition, neither condition significantly improved any post-CMJ variable. Some small improvements in jump height were observed in certain individuals after the VMAX condition, suggesting that an explosive half-squat CA may potentiate CMJ performance in certain individuals.